Formulation and Evaluation of Beta Cyclodextrin Based nanosponges Cream Formulation Containing Mometasone Furoate for Skin Disease - Kumar, Saket; Saxena, Nidhi; Jain, Ruchi; Jain, Nilesh; Goswami , R. B. (Journal of Neonatal Surgery, 2025)
The objective of this study was to develop and evaluate β-cyclodextrin (β-CD) nanosponges for the topical delivery of Mometasone furoate, a corticosteroid used for skin diseases. The nanosponges were synthesized using the hot melt method, with varying ratios of β-CD and diphenyl carbonate (DPC) as the cross-linker. Mometasone furoate was successfully loaded into the nanosponges via the freeze-drying technique. The physicochemical properties of the formulations were characterized by UV spectroscopy, FTIR, particle size analysis, zeta potential, scanning electron microscopy (SEM), and entrapment efficiency. The particle size of the formulations ranged from 131.1 nm to 217.8 nm, with formulation F5 exhibiting the smallest particle size. Zeta potential values indicated good stability, with F5 showing the highest charge (97.3 mV). The entrapment efficiency ranged from 65.4% to 96.2%, with F5 showing the highest efficiency. The formulated nanosponges were incorporated into a cream, which showed favorable characteristics such as optimal viscosity (1784 cps), pH (6.5), and spreadability (10.42 g.cm/s). The antimicrobial activity was evaluated against E. coli and S. aureus, showing significant antimicrobial effects. The formulation was also found to be non-irritant upon skin application. These results suggest that Mometasone furoate-loaded β-CD nanosponges cream could be an effective and safe formulation for the treatment of skin diseases.